A truncated fragment of Ov-ASP-1 consisting of the core pathogenesis-related-1 (PR-1) domain maintains adjuvanticity as the full-length protein. Issue 16 (15th April 2015) - Guo, Jingjing; Yang, Yi; Xiao, Wenjun; Sun, Weilai; Yu, Hong; Du, Lanying; Lustigman, Sara; Jiang, Shibo; Kou, Zhihua; Zhou, Yusen
Highlights: Ov -ASP-1, an onchocerca volvulus protein, has good adjuvanticity for protein antigens. A truncated Ov -ASP-1 (ASPPR) maintains adjuvanticity as the full-length of Ov -ASP-1. ASPPR augments humoral and cellular immune responses elicited by protein antigens. ASPPR has potential to be further developed as a novel adjuvant for human use. Abstract: The Onchocerca volvulus activation-associated secreted protein-1 ( Ov -ASP-1) has good adjuvanticity for a variety of antigens and vaccines, probably due to its ability activate antigen-processing cells (APCs). However, the functional domain of Ov -ASP-1 as an adjuvant is not clearly defined. Based on the structural prediction of this protein family, we constructed a 16-kDa recombinant protein of Ov -ASP-1 that contains only the core pathogenesis-related-1 (PR-1) domain (residues 10–153), designated ASPPR. We found that ASPPR exhibits adjuvanticity similar to that of the full-length Ov -ASP-1 (residues 10–220) for various antigens, including ovalbumin (OVA), HBsAg protein antigen, and the HIV peptide 5 (Pep5) antigen, but it is more suitable for vaccine design in ASPPR-antigen fusion proteins, and more stable in PBS than Ov -ASP-1 stored at −70 °C. These results suggest that ASPPR might be the functional region of Ov -ASP-1 as an adjuvant, and therefore could be developed as an adjuvant for human use.